Key Issues in Special Educational Needs, Disability & Inclusion. - Hodkinson, Alan; Hodkinson, Alan. (2019)
Special educational needs and inclusion can be a difficult area of study to approach for undergraduate students. This title explores and critically examines the field, providing a detailed introduction to the topic for students - helping them to develop understanding, without assuming any prior knowledge.
Previous edition: published as Key issues in special educational needs & inclusion. 2016.
Includes bibliographical references and index.
Keywords: Special education; Inclusive education; Children with disabilities -- Education; Education